1982
DOI: 10.1017/s0003356100000647
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the progeny of British Friesian dams and different sire breeds in 16- and 24-month beef production systems 2. Carcass characteristics, and rate and efficiency of meat gain

Abstract: Carcass characteristics of purebred British Friesian steers and crossbred steers by eight sire breeds out of British Friesian dams, in 16-month and 24-month beef production systems, were compared. Sire breeds included Charolais, Simmental and the main traditional British beef breeds. A total of 579 cattle were involved.The cattle were slaughtered at a fixed level of fatness and the carcasses evaluated using a standardized commercial cutting technique. Data were adjusted to equal carcass subcutaneous fat concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 20 publications
8
20
1
Order By: Relevance
“…Previous research has shown that when growing cattle of diverse breeds are compared at a similar age, with similar management, variation will be found in carcass weight, while carcass composition will depend on the range of target weights and differences in growth curves of each breed (Kempster et al 1982, Alberti, et al 2008. In agreement with our finding with grass silage-grain -based diet, Cuvelier et al (2006a) reported no differences in LWG between Aberdeen Angus and Limousin bulls fattened with a sugar-beet pulp or a cereal-based diet and slaughtered at age 530 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that when growing cattle of diverse breeds are compared at a similar age, with similar management, variation will be found in carcass weight, while carcass composition will depend on the range of target weights and differences in growth curves of each breed (Kempster et al 1982, Alberti, et al 2008. In agreement with our finding with grass silage-grain -based diet, Cuvelier et al (2006a) reported no differences in LWG between Aberdeen Angus and Limousin bulls fattened with a sugar-beet pulp or a cereal-based diet and slaughtered at age 530 days.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between individual beef breeds in performance, carcass traits and meat quality have been recently evaluated, for example, by Chambaz et al (2003), Bartoň et al (2006), Cuvelier et al (2006a,b) and Alberti et al (2008). In addition, numerous research reports have been published on the performance of different sire breeds compared in crossbreeding trials, for example, in Great Britain (Kempster et al 1982(Kempster et al , 1988, Norway (Aass andVangen 1998, Rødbotten et al 2002), Czech Republic (Sŭbrt et al 1999, Poláh et al 2004) and United States (Koch et al 1982, Wheeler et al 1996. However, in Finland, less research has been carried out, and there is a paucity of information on the effects of breed on the performance, carcass traits and meat quality of beef-breed bulls raised to heavy carcass weights with typical Finnish grass silage-grain based rations.…”
Section: Introductionmentioning
confidence: 99%
“…The AA and BB sire breeds were specifically chosen for the study because they represent extremes in fatness (at a fixed age/weight), carcass conformation and muscling (Kempster et al, 1982;Keane, 2002). These traits may be differentially affected by changes in EPD CWT .…”
Section: Discussionmentioning
confidence: 99%
“…Cross et al (1984) investigated the influence of age, breed and sex on carcass traits and meat palatability of Charolais, Simmental, Hereford and Aberdeen Angus steers. Numerous reports have been published on carcass characteristics of different sire breeds compared in extensive crossbreeding trials in Great Britain (Kempster et al, 1982(Kempster et al, , 1988, New Zealand (Everitt et al, 1980;Morris et al, 1990) and in the United States (Koch et al, 1982;Wheeler et al, 1996Wheeler et al, , 2005. Breed differences between crossbred bulls sired by different beef breeds in the Czech Republic were described by Voříšková et al (1998), Šubrt et al (1999) and Polach et al (2004).…”
mentioning
confidence: 99%